2020
DOI: 10.1111/pde.14399
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric maculopapular cutaneous mastocytosis: Retrospective review of signs, symptoms, and associated conditions

Abstract: Background/Objectives: Though maculopapular cutaneous mastocytosis is the most common form of pediatric mastocytosis, it remains unclear which patients will experience severe symptoms. We sought to better define the presentation and the cutaneous and systemic signs and symptoms in patients with maculopapular cutaneous mastocytosis. Methods: We analyzed retrospective data on 227 patients diagnosed with maculopapular cutaneous mastocytosis prior to age 15 years from five US clinical sites. We collected data on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Blistering was reported in a third of the children, flushing in 25%, gastrointestinal symptoms (abdominal pain, diarrhea, nausea) in 20%, and anaphylaxis in 5%. In other cohorts, similar, but sometimes also lower, symptom rates were observed [ 13 , 18 ]. In particular, the occurrence of anaphylactic reactions in pediatric CM varies between 0 and 9% in the literature [ 13 , 19 ].…”
Section: Symptomssupporting
confidence: 62%
“…Blistering was reported in a third of the children, flushing in 25%, gastrointestinal symptoms (abdominal pain, diarrhea, nausea) in 20%, and anaphylaxis in 5%. In other cohorts, similar, but sometimes also lower, symptom rates were observed [ 13 , 18 ]. In particular, the occurrence of anaphylactic reactions in pediatric CM varies between 0 and 9% in the literature [ 13 , 19 ].…”
Section: Symptomssupporting
confidence: 62%
“…It is a disorder that has a wide range of symptoms and therefore a broad differential diagnosis including epidermolysis bullosa, café-au-lait macules, linear immunoglobulin A bullous dermatosis, atopic dermatitis, and angioedema must be considered. 5,6 The most recent WHO classification of mastocytosis states that to diagnose pediatric cutaneous mastocytosis, there must be the typical skin lesions, a positive Darier's sign, the absence of clinical signs of systemic involvement. 7 Bone marrow biopsy is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is a disorder that has a wide range of symptoms and therefore a broad differential diagnosis including epidermolysis bullosa, café-au-lait macules, linear immunoglobulin A bullous dermatosis, atopic dermatitis, and angioedema must be considered. 5,6…”
Section: Discussionmentioning
confidence: 99%
“…Maculopapular CM (MPCM), also known as urticaria pigmentosa, with its two variants, monomorphic and polymorphic [32]. Clinically, it is recognizable for its small, monomorphic, red-brown macules/papules ,typically on the trunk, sparing face and extremities [33].…”
mentioning
confidence: 99%
“…In most cases, CM develops with a benign course and often regresses by puberty. Recent data showed that localized mastocytomas tend to regress at a rate of 10% per year (Gurnee), while MPCM presents a slower rate of 1.9% per year [32,36,37].…”
mentioning
confidence: 99%